Research on coordinated control of AC/DC system considering energy storage power limitation. (November 2022) - Li, Bowen; Sun, Yuanyuan; Li, Yahui; Lu, Tong; Yu, Tao; Pang, Yanqing
Abstract: Energy storage can effectively alleviate the power fluctuation caused by high permeability distributed new energy in AC/DC system. However, due to the state of charge (SOC) of energy storage, AC/DC system is difficult to give full play to the power complementary. Thus, a coordinated control strategy of AC/DC system considering the state of charge of energy storage is proposed in the paper. Firstly, the power balance between subnets of AC/DC system is analyzed to achieve the balance of supply and demand. Then, according to the power control strategy, the AC/DC coordinated control strategy based on energy storage SOC is studied. In order to improve the stable operation ability of the system, the technology of virtual synchronous generator (VSG) is applied. Finally, the validation model is built based on MATLAB/ Simulink platform. The simulation results show that the strategy can effectively coordinate the power interaction between the subnet power supply and the interconnected converter and improve the system stability.